Pharmacological treatment of epilepsy in elderly people, a literature review. - Bombón-Albán, Paulina E. (2022)
Elderly people are at a higher risk of developing epilepsy. With a progressive increase in life expectancy, this is the fastest growing group of epilepsy patients. Their treatment is complicated by the presence of physiological changes related to aging, comorbidities, concomitant cognitive problems, complex drug interactions, and difficulties in the adherence to medication regimes. Seizures can be controlled in elderly people patients with low doses of a single epileptic seizure drug. Tolerability is an important factor in drug selection, as elderly people patients tend to be very sensitive to side effects. Enzyme-inducing anti-seizure drugs should gradually be left out of the therapeutic arsenal in favor of new anti-seizure drugs that have shown similar efficacy and better tolerability. Levetiracetam and lamotrigine are the most recommended anti-seizure drugs for elderly people with epilepsy nowadays. Although it could be easily controlled, it is recommended that elderly people continue their treatment indefinitely, due to the recurrent seizures’ proclivity. More studies are needed to address the pathophysiological mechanisms of epilepsy in this age group, and greater inclusion of elderly people in clinical trials is needed, as is the development of comprehensive care models to provide optimal patient care.